MECONIUM ASPIRATION SYNDROME: AN EXPERIENCE IN NEONATOLOGY DEPARTMENT OF CHILDREN HOSPITAL LAHORE - Khan, Imran; Gul, Haji (Journal of Postgraduate Medical Institute, 2017)
Objectives: To determine the frequency of complications like air leak syndrome and persistent pulmonary hypertension (PPHN) in neonates with meconium aspiration syndrome in Children Hospital Lahore. Methods: A descriptive cross sectional study was conducted in Neonatology Department of Children Hospital, Lahore from 10th august 2013 to 10th February 2014. All patients having meconium aspiration syndrome (MAS) who survived with age <28 days were included and those patient who were having MAS but were treated in emergency or those who could not survived were excluded from the study. A total of 150 patients were enrolled in the study. Data were collected on a predesigned profarma and analyzed using SPSS software version 18. Data were then presented in the form of figures. Results: Out of 150 patients, 63 babies (42%) developed PPHN and 22 babies (14.6%) suffered from air leak syndrome. There were 102(68%) male patients and 48(32%) patients were female patients. 88 patients (58.6%) were born at term and 62 patients (41.3%) were post term. Conclusions: Pulmonary hypertension was the most common complication followed by air leak syndrome. It was more common in male patients as compared to females.